An introduction to clinical practice guideline for Chinese undergraduates in stomatology. (5th October 2013) - Li, C.; Zheng, J.; Guo, C.; Ling, J.; Yu, H.; Zhang, J.; Tai, B.; Hou, T.; Tang, G.; Sun, W.; Wang, S.
Abstract The Society of Dental Education, Chinese Stomatological Association has formulated the Standards of Clinical Practice for Chinese Undergraduate Students Majoring in Stomatology, on the basis of extensively soliciting the views of experts in various fields. The aim of this standard is to guide clinical teaching and improve teaching quality in schools of stomatology in China. The standards include eight parts: the standard of clinical practice for oral and maxillofacial surgery, for cariology and endodontics, for periodontics, for the oral mucosa diseases, for preventive dentistry, for pedodontology, for prosthodontics and for oral imageology. Each part includes introduction to subjects, the clinical practice time period, the purpose and requirements of practice, the disease types of practice and items of clinical operation, the index of the lowest workload of practice and the major methods of assessment. These standards are not only the basic requirements and guiding principles for clinical teaching, but also the major criteria for assessing the clinical teaching quality of stomatological colleges/schools of China.